1999
DOI: 10.1145/316194.316211
|View full text |Cite
|
Sign up to set email alerts
|

Proportional differentiated services

Abstract: Internet applications and users have very diverse service expectations, making the current same-service-to-all model inadequate and limiting. In the relative differentiated services approach, the network traffic is grouped in a small number of service classes which are ordered based on their packet forwarding quality , in terms of per-hop metrics for the queueing delays and packet losses. The users and applications, in this context, can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…The Random-Move scheme consists of a 3x3 mobility cell scenario (with one base station in the center of each cell) where eight cells (2)(3)(4)(5)(6)(7)(8)(9) are in use (cf., Fig. 11).…”
Section: Simulation Modelmentioning
confidence: 99%
“…The Random-Move scheme consists of a 3x3 mobility cell scenario (with one base station in the center of each cell) where eight cells (2)(3)(4)(5)(6)(7)(8)(9) are in use (cf., Fig. 11).…”
Section: Simulation Modelmentioning
confidence: 99%
“…A simulation study of DiffServ with both delay and loss QoS classes is found in [44]. A controllable DiffServ mechanism is Proportional Differentiated Services [18], which aims to quantitatively differentiate the QoS among the classes relative to some predefined parameters. Many other scheduling mechanisms that limit the delay of a selected flow keep track of a 'deadline' for each queued packet, such as earliest deadline first (EDF) [43,38] and alternative best-effort [26] or use virtual clocks [52].…”
Section: Introductionmentioning
confidence: 99%
“…DiffServ has sacrificed accuracy to improve scalability of IntServ architecture. In many recent works the DiffServ accuracy is strengthened besides reduction in the complexity of the network especially at core routers (Dovrolis, 2000;Mahramian, Taheri, & Haeri, 2005;Stoika & Zhang, 1998;Striegel & Manimaran, 2002). They assume nothing about traffic shaping and minimize or avoid on line negotiations about traffic conditions between routers.…”
Section: Introductionmentioning
confidence: 99%
“…An idea to increase QoS accuracy while preventing complexity was proposed by Dovrolis (2000). He assumed proportional delay and loss guarantees for different traffic classes instead of an absolute delay or loss for each class.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation